CHARACTERIZATION OF CLAY MATERIALS USED FOR POTTERY PURPOSES FROM RENDENG, MALO, BOJONEGORO - Setyaningrum, Dyah; Sujiat, Sujiat; Azizah, Aprilia Nur (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Clay material from Rendeng, Malo, Bojonegoro was studied by mineralogy and physicochemical characterization to evaluate its potential suitability as a raw material in pottery application. X-ray Diffraction (XRD) and Fourier Transform-Infrared (FTIR) spectrometry were used to establish the mineralogy composition. Meanwhile the physical properties were identified by particle size distribution and consistency limits. Chemical composition was carried out by X-ray Fluorescence Spectrometer (XRF).Â The results of XRD characterization revealed that clay from Rendeng Village, Malo, Bojonegoro containedÂ kaolin, quartz, and feldspar. Physical characterization shows that clay material is a less plastic type based on Atterberg method. Based on the chemical compositions indicated that SiO2, Al2O3, CaO, and Fe2O3 were abundance oxides. Therefore, clay from Desa Rendeng was only suitable for the pottery purposes because most of its mineral compositions did not meet the quality requirements for making advanced ceramics.